Countermovement jump characteristics of world-class elite and sub-elite male sprinters - Beattie, K.; Tawiah-Dodoo, J.; Graham-Smith, P. (Sport Performance & Science Reports, 2020)
World-class 100m sprinters need a combination of exceptional acceleration, maximum-velocity and speed-endurance; each of which are dictated by their own complexi interplay of physiological and biomechanical factors. Previous research has highlighted the importance of lower-limb force production, and the direction of application, for elite sprint performance. The countermovement jump (CMJ) is a popular explosive-strength assessment often utilised by coaches and sport scientists to ascertain an athlete`s ability torapidly apply vertical force with their lower limbs. Compared to other strength diagnostic tests, the CMJ is highly practical due to its simplicity, low physiological strain, cost-and time-effective technology (i.e. smartphone app, contact mat, portable force platform). The CMJ can be used to monitor explosive-strength adaptation, direct gym programming and infer neuromuscular readiness of an athlete. In sprinters, previous research has found strong relationships between specific CMJ variables (i.e. jump height, peak power) and both acceleration (r = 0.52-0.86) and maximum-velocity performance (r = 0.55-0.77). Consequently, depending onother confounding factors (i.e. sprint technique, anthropometrics, level of performance), it may be suggested that 30-75% of sprint performance variance is explained by explosive-strength. However, previous research has mainly focused on sub-elite populations (100m personal best [PB]>10.28s) and there is a lack of literature investigating the CMJ characteristics of world-class elite male sprinters (100mPB<10.15s).